2007
DOI: 10.1016/j.bbrc.2007.02.070
|View full text |Cite
|
Sign up to set email alerts
|

C-Npys (S-3-nitro-2-pyridinesulfenyl) and peptide derivatives can inhibit a serine-thiol proteinase activity from Paracoccidioides brasiliensis

Abstract: The inhibitory capacity of C-Npys (S-[3-nitro-2-pyridinesulfenyl]) derivatives over thiolcontaining serine proteases has never been tested. In the present work we used an extracellular serine-thiol proteinase activity from the fungal pathogen Paracoccidioides brasiliensis (PbST) to describe a potent inhibitory capacity of Bzl-C(Npys)KRLTL-NH 2 and Bzl-MKRLTLC(Npys)-NH 2 . The assays were performed with PbST enriched upon affinity chromatography in a paminobenzamidine (pABA)-Sepharose column. Although PbST can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…The inhibitory potency of the Npys derivative compared to the thiol‐containing serine proteases was demonstrated by Matsuo et al using the fungal pathogen Paracoccidioides brasiliensis . The protease activity was impaired by conjugation of a small Cys(Npys)‐containing hexapeptide . Matsueda's group also showed that the controlled introduction of Npys at selected peptides provided selective platelet calpain inhibitors that did not inhibit the functions of other proteins, such as thrombin, by selectively delivering the Npys group.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory potency of the Npys derivative compared to the thiol‐containing serine proteases was demonstrated by Matsuo et al using the fungal pathogen Paracoccidioides brasiliensis . The protease activity was impaired by conjugation of a small Cys(Npys)‐containing hexapeptide . Matsueda's group also showed that the controlled introduction of Npys at selected peptides provided selective platelet calpain inhibitors that did not inhibit the functions of other proteins, such as thrombin, by selectively delivering the Npys group.…”
Section: Introductionmentioning
confidence: 99%